ICTs IN INCLUSIVE EDUCATION: INTERNATIONAL EXPERIENCE (Journal of Educational Sciences, 2020)
Inclusive education – ensuring equal access to education for all learners, taking into account the diversity of special educational needs and individual opportunities. People with disabilities need to acquire the fundamental knowledge that enables survival in society under the specific demands caused by functional limitations that hinder participation in ordinary education systems. ICTs are powerful sup¬porting tool in inclusive education. Nowadays ICT has become an important element of the learning and teaching process. A lot of ICT tools are used in inclusive education. It is neccessary comparing and analyzing international practice of using ICT in inclusive education to create educational program with ICT tools for all children. Authors showed to what extent ICT in inclusive education can be used effectively and in innovative ways in relation to four thematic areas that emerge from a consideration of the key messages within the UN Convention. In total, about ten countries and their positive experience were reviewed. Key words: inclusive education, information and communication technologies, training pedagogies, international experience.